Features of the pathogenesis, diagnosis and treatment of myocardial ischemia with non-obstructive coronary arteries - E. A. Khachirova; M. D. Iarovoi (Евразийский Кардиологический Журнал, 2025)
Among the most dangerous causes of mortality worldwide, coronary artery disease (CAD) remains the leading cause. Despite the fact that atherosclerosis of the coronary arteries is the main cause of the development of coronary artery disease, clinicians are increasingly identifying myocardial ischemia without coronary obstruction. Myocardial ischemia with non-obstructive coronary arteries (INOCA) is characterized by clinical signs of myocardial infarction (MI) with evidence of coronary artery stenosis on angiography of less than 50%. In recent years, significant advances have been made in understanding the pathophysiological changes that underlie this condition, but the predictors of development of this condition remain unclear. And a diagnosis of INOCA remains a difficult task for the clinician to this day. Determining the mechanism of INOCA and excluding other possible causes of elevated cardiac troponin is important for the development of secondary prevention measures aimed at improving the prognosis of patients after acute myocardial infarction (AMI). A history of disease and use of invasive and noninvasive imaging should lead to the identification of possible vasospastic or microvascular causes of INOCA and their differentiation from myocardial injury caused by other diseases. Compared with patients with AMI due to obstructive coronary artery disease (CAD), patients with INOCA are more often women and tend to have fewer traditional cardiovascular disease (CVD) risk factors.The aim of this article was to review the literature and evaluate the clinical features, ethiology, diagnosis, treatment, and prognosis of INOCA. This review summarizes the current knowledge of INOCA in the areas of epidemiology, pathophysiology and treatment, with an emphasis on modern diagnostic tools for this disease.